Alih Media Arsip Vital sebagai Upaya Preservasi Arsip di Balai Diklat Industri (BDI) Surabaya - Thariq Hidayatullah; Tatiana Kristianingsih (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This study aims to determine how the process of media transfer of vital archives as an effort to preserve archives at the Surabaya Industrial Training Center. The study used a qualitative approach and involved BDI Surabaya archivists as research subjects. Data were obtained through interviews, observations, and documentation. The results of the study showed that the media transfer process had three main stages, such as pre-media transfer, implementation of media transfer, and post-media transfer. Vital archives that were transferred included important documents such as decrees of the head of the training center, land and building certificates, and cooperation agreements or MoUs. This study recommends improving facilities and infrastructure, developing the capacity of archivists, and improving the storage system so that digital archive management is more optimal in the future.